Discovering The Significant Potential of Edible Insects In Food, Feed, And Drug Security - Elias Mjaika Ndifon; Chidiebere Prince Osuji Emeka; Paul Inyang; Emmanuel Ankrumah (University of Sultan Ageng Tirtayasa, 2024)
Practice of entomophagy is mainly constrained by socio-economic factors and climate. Knowledge on the practice of entomophagy is scarce globally. Structured questionnaires (560 pieces) were effectively administered in six states (ten Local-Government Areas i.e. 14 sampled towns) in mainly Eastern Nigeria to determine the status of entomophagy. Consumption of termites occurs in 61% of these states; followed by green grasshoppers (36%), palm weevils (33%), honeybees (23%), and African crickets (20%). About 73.7% of the respondents have eaten insects and 47.9% of them have edible insects they prefer. Based on the separation of means, using the most consumed, rearable, preferred appetizing insect to eat, and market: termites came top followed by green grasshopper – which was at par with palm weevils, then honeybees. The sale of insects in the region was acknowledged by 66.7% of the respondents. Most of the respondents (92.0%) have never witnessed anyone falling ill due to the consumption of insects. No insect consumption taboo was reported in the region. Therapeutic use of insects was reported by 86.9% of the respondents. Most of the respondents (64%) are knowledgeable about use of insects as feedstuff. The insect industry still rely on capturing insects using nets (70%), light-water-basin traps (90%), hand-picking (80%), pursuing/chasing insects (50%) and lastly digging the insects from their habitats/soil/trees (20%). Insects are prepared for consumption by frying (50% of the states), sun-drying (80%), salting (30%), smoking (10%). Respondents advised that educating the inhabitants on potentials of insects and improved method of preparing the insects should be encouraged.